The Oncology Data Network (ODN): Methodology, Challenges, and Achievements. (21st May 2020) - Woolmore, Ashley; Arnold, Dirk; Blay, Jean‐Yves; Buske, Christian; Carrato, Alfredo; Gerritsen, Winald; Peeters, Marc; Garcia‐Foncillas, Jesus; Kerr, David
Abstract : Open to all European cancer centers, all cancer patients, and all cancer types, the Oncology Data Network (ODN) aims to create an extensive infrastructure of real‐world cancer care information. This article describes the ODN's methodological approaches, challenges, and achievements to date.